Get ready! for standardized tests. Grade three / Math - Osborne, Susan (New York : McGraw-Hill, 2001)
Contains sample questions, test-style exercises, and study guides designed to help students in third grade prepare for standardized tests.
"Real sample test"--Cover.
Cover title: Get ready! for standardized tests.
Includes bibliographical references (p. 67).
Professional
Keywords: Achievement tests -- United States -- Study guides; Mathematics -- Study and teaching (Elementary) -- United States; Mathematics -- Study and teaching -- Parent participation -- United States; Achievement tests -- United States -- Study guides; Mathematics -- United States -- Examinations -- Study guides; Mathematics -- United States -- Study and teaching